Maturation and Spawning of Green – Rough – Back Pufferfish, Lagocephalus lunaris - Rukmini Sirisha; . Imandi; Poturaju Yedukondala Rao (New Visions in Biological Science Vol. 4, 2021)
Studies on maturation, spawning and fecundity are essential for estimation of reproductive potential of a population as well as fishery management. Maturation and spawning of the puffer fish Lagocephalus lunaris was reported from Visakhapatnam during January 2008 to December 2009 to understand reproductive potential of their population. The present observations showed that males are smaller than females. Sex-ratio indicated that females were dominant in the catches and the sex ratio for male to female was 1: 1.17. Chi-square (X2) analysis showed that there was a significant difference (p< 0.05) between sexes in their occurrence during April 2008, November 2008 and June 2009. The size at first maturity was found to be 141 mm total length for females of L. lunaris. A scale of six stages of maturity of gonads has been identified in females of L. lunaris. Spawning takes place throughout the year with peak during April to June and September to December. Gonad Somatic Index has been found to be high during January, April, June, September and December in females. Fecundity varied from 103355 to 298795 ova.